From brick-and-mortar to online teaching during the COVID-19 pandemic lockdown in Osun state, Nigeria - Opesemowo, Oluwaseyi Aina; Obanisola, Akin; Opesesmowo, Titilope Rachael (Journal of Education in Black Sea Region, 2022)
This study examined the private secondary school students’ perception, satisfaction, and attitude towards online teaching. Some information concerning online teaching during the COVID-19 pandemic lockdown in Osun state, Nigeria was provided. The descriptive survey design was adopted for this study. The population comprised all private secondary school students in Osun state, Nigeria. A simple random sampling was used to select 664 students from four private senior secondary schools across the state. A self-developed 21-item instrument with a Cronbach alpha of 0.84 was used to elicit information from the participants. Data were analyzed using chi-square statistic at 0.05 level of significance. The result revealed that most private secondary school students had high perceptions of online teaching as well as a positive attitude towards online teaching. There was a statistically significant relationship between participants’ school class (χ2 = 11.08; p < 0.05) and satisfaction level towards online teaching, while there was no significant association between respondents’ gender (χ2 = 2.38, p > 0.05), age (χ2 = 0.07, p > 0.05) and satisfaction levels towards online teaching. It was concluded that online teaching should be used to teach private secondary school students in addition to brick-and-mortar teaching.